TO THE JUBILEE OF PROFESSOR STEPANOVA ELEONORA FEDOROVNA - D. V. Kompantsev; V. M. Kishchenko; D. V. Veselova; K. N. Koryanova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2018)
The article is devoted to the anniversary of Professor Eleonora Fedorovna Stepanova - a bright representative of the Russian intelligentsia: a talented lecturer, an inventor, an author of numerous books, an internationally recognized scholar!